2015
DOI: 10.1586/14779072.2015.1026259
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of rivaroxaban in real-life patients with atrial fibrillation

Abstract: Rivaroxaban is a once-daily oral anticoagulant currently marketed for the prevention of stroke and systemic embolism in patients with non-valvular atrial fibrillation. This indication is largely based on the results of the ROCKET-AF trial. Although these results are robust, studies performed in clinical practice are necessary to confirm these data in real-life patients. These studies have shown rates of stroke and bleeding similar to that found in ROCKET-AF. As an anticoagulant, attention should be paid to mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…8,9 Several recent studies of DOACs in ‘real-world’ clinical settings have shown similar efficacy and safety to the RCTs, but these were not designed to investigate interacting drugs. 1015 Some data are available on clinical outcomes of specific PK-DDIs with DOACs but the evidence is conflicting. For example, amiodarone has been associated with increased odds of bleeding in patients taking rivaroxaban, 16 and patients who had major bleeds on rivaroxaban appeared twice as likely to be taking a P-gp inhibitor with or without a CYP3A inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Several recent studies of DOACs in ‘real-world’ clinical settings have shown similar efficacy and safety to the RCTs, but these were not designed to investigate interacting drugs. 1015 Some data are available on clinical outcomes of specific PK-DDIs with DOACs but the evidence is conflicting. For example, amiodarone has been associated with increased odds of bleeding in patients taking rivaroxaban, 16 and patients who had major bleeds on rivaroxaban appeared twice as likely to be taking a P-gp inhibitor with or without a CYP3A inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…The ROCKET AF trial represents a landmark trial establishing the use of rivaroxaban as an effective and well-tolerated alternative oral anticoagulant to warfarin in patients with AF. Recent analyses have reinforced the robustness of the results of the ROCKET AF trial and suggest that the results hold up well in real life clinical practice [Martinez-Rubio et al 2014; Baron-Esquivias et al 2015]. The results from the ROCKET AF trial parallel those from other major trials establishing the use of NOACs in AF patients [Connolly et al 2009; Granger et al 2011; Giugliano et al 2013].…”
Section: Resultsmentioning
confidence: 86%
“…This approval was based on the ROCKET-AF results [59]. Patients included in clinical trials usually differ somewhat from those attended in daily clinical practice [94,95]. Consequently, studies performed in the clinical practice setting are very relevant.…”
Section: Efficacy and Safety Of Rivaroxaban In 'Real-life' Patients Witmentioning
confidence: 99%